Hashtags sob o viés da semântica da enunciação - Claudiene Diniz da Silva (2017)
This thesis presents a study about the hashtag, defined as a word or expression preceded by the symbol (#) much recurrent in the internet, more specifically, in virtual social networks, with several functionalities. The basic functions of the hashtag are providing and joining common information, grouping messages and people who deal with common issues; advertising and promoting brands, campaigns, events and being used for playful purposes such as games, jokes and humor. In order to carry out a study of this linguistic form which permeates the digital world and its outer part, we adopt as a theoretical reference the Semantics of the Enunciation by Guimarães (1996, 2002) and Dias (2009, 2013, 2015), inspired by some concepts of the French linguists Emile Benveniste and Oswald Ducrot. Bearing on mind the adopted theory, we propose a study of the hashtag to understand its enunciative functioning, especially the enunciative reasons of this linguistic form, focusing on the notions of historical reference and enunciative pertinence. Thus, in the first chapter, we present a broad description of the hashtag, using the available bibliography about this subject. In the second chapter, we present the theoretical assumptions of the Semantics of Enunciation, presenting the concepts of enunciative event, historical referential, enunciative pertinence of ordering and enunciative agency, essential for our data analysis. The third chapter is an exposition of hashtag analogies as other linguistic forms with which it bears some similarity. In relation to the methodological assumptions, we adopted a study of enunciative networks and compile a corpus of cyber-canonical hashtags to explain how the enunciation process occurs. Thus, our analysis presents an enunciative study of hashtags that deal with politics, homophobia, racism, pedophilia and environmental disaster. Our analyzes show that the hashtag is produced motivated by a social need, called by Dias (2015b) of present demand of the saying. This demand inserts the hashtag into an enunciative event that is marked by a historical reference and by pertinences of enunciative ordering and agency. With this, we identify the importance of the notions of historical reference and relevance to the meaning of the hashtag. The analyzes also show the similarities between the hashtag and the noun, since both have the ability to condense words. In addition, our research demonstrates how hashtag is a form that breaks the patterns of traditional writing and relates to other elements, especially multimodal ones, and this fosters other sense-building strategies.